Effects of Brazing Technology on Hermeticity of Alumina Ceramic-Metal Joint Used in Nuclear Power Plants - Deng, Nengmei; Zhao, Jun; Yang, Lilin; Zheng, Zhiqin (Frontiers in Materials, 2021)
Taking the brazing mechanism of alumina ceramics and kovar alloys as the main research object, which is based on the molybdenum-manganese metallization method. And the influence of direct brazing process and indirect brazing process on the morphology of the final connected layer was explored. Combined with SEM, EDS, the microscopic morphology and hermeticity affecting the final ceramic-metal composite component was discussed. Finally, through the indirect brazing process, various ceramic-metal composite joints with good airtightness satisfying the requirements were prepared.